Developing Advertisment Material for Different Learning Styles of Students Based Canva Power Point - Ningsih, Sry Rahayu; Hasibuan, Ahmad Laut; Asnawi, Asnawi (PT Inovasi Pratama Internasional, 2025)
This research focuses on the design of developing advertising materials tailored to various learning styles among grade nine students at SMP N 2 Perbaungan, Serdang Bedagai Regency. Recognising the diversity in learning preferences of visual, auditory, and kinesthetic students, this research aims to create Advertising materials using Canva's PowerPoint (PPT) to effectively address and engage various learning styles are more effectively. This research follows a research and development (R&D) methodology, using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to design the materials. Through analysis, students' predominantly visual, auditory, and kinesthetic learning styles can be identified to guide the material development process. The resulting materials are intended to be visually appealing, interactive, and flexible, which improves comprehension and retention. Data collected through student feedback, teacher evaluations, and pre- and post-assessment scores indicate that the customised materials have a positive impact on students' engagement and understanding of advertising concepts to enhance the learning experience and accommodate individual needs in a classroom setting.The results of the validator test of the overall media design meet the eligibility criteria (88.9%) so that the teaching materials can be used as teaching materials for students in the learning process. The results of the assessment of English teaching materials by experts regarding the substance of the material as a whole from the aspects assessed get the eligibility criteria (87.5%) so that the teaching materials can be used in the learning process. and the trial results show the average student score of 81. 18% so that the criteria for effective teaching materials for different learning styles of students by using advertisements on writing skills in class IX SMPN 2 Perbaungan. research and development, implementation and evaluation) The instruments used are questionnaires to students, interviews to teachers, and the results of the last trial given to students.